(untitled) (Research, Society and Development, 2021)
Medicinal plants have been used for a long time by our ancestors, and their knowledge and practices have been passed on from generation to generation, a habit that only tends to increase day by day, mainly because they are easily accessible, and can even be cultivated in the backyard of the house itself. Given the current scenario of the pandemic, caused by SARS-CoV-2, many people have looked to them for disease prevention, symptom relief or even a cure. In view of the facts presented, the objective of this work was to evaluate, through an online questionnaire on Google Forms, shared via social media, the use of medicinal plants against Covid-19, prevention, relief of symptoms, if there was a significant increase of use, and show the precautions that should be taken with their indiscriminate use. The data obtained were quantitatively evaluated. A review of national and international literature was carried out using published articles, addressing the importance of medicinal plants, their effectiveness in terms of their use in diseases caused by viruses and the use of herbal products in Brazil. It can be concluded that medicinal plants are widely used by the population, especially when it comes to preventing some disease, such as Covid-19, however, even though medicinal plants are effective and widely used, care must be taken with their use and do not despise scientific knowledge.